INFLUENCE OF SEEDING RATES ON LODGING AND YIELD OF DIFFERENT OAT CULTIVARS - A. M. S. Addaheri; E. K. Mahmood; A. Ch. Al-Fahad (مجلة الأنبار للعلوم الزراعية)
This study investigated the potential for controlling lodging by manipulating the seeding rates for oat cultivars introduced in Iraq. A field experiment was conducted in the winter 2022-23 at one of the agricultural fields in Ramadi, in the western region of Iraq. Split-plot arrangement in a randomized complete block design (RCBD) with three replications was used. The first factor included the three Carrolup, Genzania, and Hamel oat cultivars. The other experimental factor was seeding rates of 60, 80, and 100 kg ha-1. The findings showed that the Hamel cultivar had the largest average stem diameter while the Genzania produced the greatest dry matter and grain yields. The seeding rate of 60 kg ha-1 had the lowest plant height, lodging index and dry matter, and largest stem diameter. The 100 kg ha-1 seeding rate had the greatest plant height, lodging index, and grain yield, and lowest stem diameter. Lowering the seeding rate from 100 to 80 kg ha-1 led to a reduction in lodging by 13.9% without deteriorating dry matter and grain yield while reducing it to 60 kg ha-1 led to a reduction in lodging, and dry matter and grain yields. This study thus recommends adopting the seeding rate of 80 kg ha-1 for growing oats in the western regions of Iraq